EFEKTIVITAS PORTAL SIMPROLAMAS DALAM ANGGARAN KEAGAMAAN PADA MODIN DI KOTA SURABAYA - Zalliety, Amadea (Program Pascasarjana Universitas Wijaya Putra Surabaya, 2025)
The utilization of the simprolamas portal for reporting religious activities that have been carried out by modins is an important part of the verification process so that later honorariums can be disbursed to modins in the city of Surabaya. This portal is designed as a digital solution to improve the efficiency, transparency, and accountability of reporting modin activities, which were previously done manually. The research method used is a qualitative approach with data collection techniques through semi-structured interviews and non-participatory observations. The results showed that the Simprolamas portal has great potential to accelerate the process of reporting and disbursing modin honorarium, but its implementation faces several challenges. The age of users (40-70 years old), low digital literacy, limited supporting tools such as low specification cellphones, and internet network constraints are the main obstacles in using this portal. Analysis using the Technology Acceptance Model (TAM) reveals that the level of Perceived Usefulness (PU) and Perceived Ease of Use (PEU) of this portal still needs to be improved to achieve wider acceptance by users. The successful use of simprolamas is an important factor in the disbursement of honorarium which is in the religious budget.